Treatments for Acute Bipolar Depression: Meta-analyses of Placebo-controlled, Monotherapy Trials of Anticonvulsants, Lithium and Antipsychotics - Selle, V.; Schalkwijk, S.; Vázquez, G. H.; Baldessarini, R. J. (Pharmacopsychiatry, 2014)
Optimal treatments for bipolar depression, and the relative value of specific drugs for that purpose, remain uncertain, including agents other than antidepressants.We searched for reports of placebo-controlled, monotherapy trials of mood-stabilizing anticonvulsants, second-generation antipsychotics, or lithium for acute major depressive episodes in patients diagnosed with type I or II bipolar disorder and applied random-effects meta-analysis to evaluate their efficacy, comparing outcomes based on standardized mean drug-placebo differences (SMD) in improvement, relative response rates (RR), and number-needed-to-treat (NNT).We identified 24 trials of 10 treatments (lasting 7.5 weeks, with ≥50 collaborating sites/trial) that met eligibility criteria: lamotrigine (5 trials), quetiapine (5), valproate (4), 2 each for aripiprazole, olanzapine, ziprasidone, and 1 each for carbamazepine, lithium, lurasidone, and olanzapine-fluoxetine. Overall, pooled drug-over-placebo responder-rate superiority (RR) was moderate (29% [CI: 19–40%]), and NNT was 8.2 (CI: 6.4–11). By SMD, apparent efficacy ranked: olanzapine+fluoxetine≥valproate>quetiapine>lurasidone>olanzapine, aripiprazole, and carbamazepine; ziprasidone was ineffective, and lithium remains inadequately studied. Notably, drugs were superior to placebo in only 11/24 trials (5/5 with quetiapine, 2/4 with valproate), and only lamotrigine, quetiapine and valproate had > 2 trials. Treatment-associated mania-like reactions were uncommon (drugs: 3.7%; placebo: 4.7%).Controlled trials of non-antidepressant treatments for bipolar depression remain scarce, but findings with olanzapine-fluoxetine, lurasidone, quetiapine, and perhaps carbamazepine and valproate were encouraging; lithium requires adequate testing.
Keywords: anticonvulsants; antipsychotics; bipolar depression; controlled-trials; lithium; meta-analysis